Construction of Smart Campus in Higher Vocational Colleges based on the Era of "Internet+" - Li, Huijuan (Journal of Theory and Practice of Contemporary Education, 2024)
Based on the research on the construction of smart campus in higher vocational colleges in the era of "Internet+", grasp the significance of smart campus, analyze the external conditions for the construction of smart campus in higher vocational colleges, and combine the problems existing in the construction of smart campus in higher vocational colleges in China, we can build a perfect network communication platform, enrich teaching resources, build an advanced integrated information query system, establish a perfect organizational structure Construction measures such as building an Internet learning and communication platform, reasonable distribution of information-based teaching resources, and strengthening students' awareness of network security and prevention, comprehensively elaborate the importance of building smart campuses in higher vocational colleges in the era of "Internet+".